The Influence of Spirituality on The Education of Muslim Micro Small And Medium Entrepreneurs In Jombang, Indonesia - Samsul Ma'arif; Muhamad Abdul Majid; Dzikrulloh Dzikrulloh (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
This research aims to analyze the influence of spirituality on entrepreneurial education for micro, small and medium enterprises. The research method used is quantitative. Data collection was carried out by distributing questionnaires in the form of closed questions in the form of a Likert's Scale to 70 respondents who were employees and customers of UMKM Kalimalang Pulo Lor Jombang. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. Consisting of validity tests, reliability tests and simple linear regression analysis. The results of the research concluded that there is an influence of spirituality on entrepreneurial education for micro, small and medium enterprises in UMKM Jombang, Indonesia. These results can be proven by a simple linear regression test on the T test table with a value of 8.666 - 1.994 with a significant value of 0.000 - 0.05. So there is a positive influence of Spirituality on the development of Muslim micro, small and medium enterprises in UMKM Jombang, Indonesia. (Ho) is accepted, and (Ha) is rejected.